KEMUNGKINAN BERHAJI DI LUAR ZULHIJJAH Perspektif Qathi dan Zhanni - Hamid, Abdul (IAIN Pekalongan, 2014)
This study examines more deeply about the addition time of the pilgrimage. There are two issues: first, whether the arguments talking about a pilgrimage are definitive (qat’i). Second, if difficulties experienced by pilgrims can be a legal basis for granting relief in prolonging pilgrimage. This review concluded that pilgrimage is only on Zulhijjah and cannot be stretched to three months due to its definitve arguments. The concept of benefit cannot change that.